2009
DOI: 10.1002/jmv.21673
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of species D human adenoviruses in fecal specimens from Urban Kenyan children with diarrhea

Abstract: Human adenoviruses (HAdVs) cause a wide range of clinical syndromes and are classified in seven species, A-G, comprising 52 serotypes. HAdV-A31, -F40, and -F41 have been associated with diarrhea in infants and young children. In developing countries gastroenteritis is a major cause of morbidity and mortality in children and, in comparison to rotaviruses, there are no data on the HAdVs associated with diarrhea in pediatric patients in Kenya. This study investigates the prevalence and genotypes of HAdVs in 278 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 43 publications
6
27
1
Order By: Relevance
“…Verma et al (49) on May 11, 2018 by guest http://jcm.asm.org/ adenovirus serotypes (7.7%) associated with acute gastroenteritis in infants and children in western India, but the strains were not further characterized. The prevalence of species D human adenoviruses was found to be high in Kenyan children with diarrhea (26). In this study, PCR-based sequence analysis of genomic DNA of adenoviruses confirmed that serotype 41 is more prevalent (68%), followed by serotype 40 (32%).…”
Section: Discussionsupporting
confidence: 63%
“…Verma et al (49) on May 11, 2018 by guest http://jcm.asm.org/ adenovirus serotypes (7.7%) associated with acute gastroenteritis in infants and children in western India, but the strains were not further characterized. The prevalence of species D human adenoviruses was found to be high in Kenyan children with diarrhea (26). In this study, PCR-based sequence analysis of genomic DNA of adenoviruses confirmed that serotype 41 is more prevalent (68%), followed by serotype 40 (32%).…”
Section: Discussionsupporting
confidence: 63%
“…Various sampling strategies and detection methods limited the feasibility of direct comparison of our cross-sectional study to other studies (Additional file 1: Table S1) [22,23,25-35]. Study participants were within limited age groups, showed specific symptoms and/or different life styles.…”
Section: Discussionmentioning
confidence: 99%
“…Hence it has been proposed that recombination might play a greater role in HAdV-D evolution than base substitution [6]. Since HIV/AIDS as well as gastroenteritis are common diseases in Sub-Saharan Africa and PCR-based and sequence-confirmed studies on the prevalence of HAdV-D in Sub-Saharan Africa are scarce [22,23], we analyzed the occurrence of HAdV-D in people from four Sub-Saharan countries; the CĂŽte d’Ivoire (CI), the Democratic Republic of the Congo (DRC), the Central African Republic (CAR), and Uganda (UG). We assessed possible connections between HAdV-D shedding and clinical symptoms or demographic data, and in addition, we partially characterized the molecular isolates by comparison of minimum genetic distances within the pV-hexon gene block.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in sub-Saharan Africa report a high prevalence of adenovirus in pediatric stool samples and the detection of adenoviruses in various types of environmental samples. 76–78 These viruses are relatively persistent in various environmental media, and infections may occur year-round. 79 Adenoviruses 40 and 41 may be used as markers of human fecal contamination.…”
Section: Methodsmentioning
confidence: 99%